THE EFFECT OF INTERNAL AUDIT ON FRAUD PREVENTION AND TRANSACTION SECURITY IN DIGITAL PAYMENTS: A SYSTEMATIC LITERATURE REVIEW - Nur Azkiyah Djafar; Sitti Fatira Gumohung; Kiki Amelia Bilondatu; Ahmad A. Umar; Shaman Noholo (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The rapid development of digital payments has made financial transactions easier, but it has also increased the risk of fraud and threats to transaction security. This article aims to analyze the influence of internal audit on fraud prevention and transaction security in digital payment systems through a Systematic Literature Review (SLR) approach. The study was conducted by reviewing various literature discussing the role of internal audit, fraud prevention, and digital transaction security. The results indicate that internal audit plays a crucial role in identifying risks, evaluating the effectiveness of internal controls, and supporting fraud detection and prevention through the use of digital technologies such as continuous auditing, data analytics, and real-time transaction monitoring. Furthermore, integrating internal audit with robust control systems and adequate security technology can improve transparency, accountability, and transaction security in digital payments. Thus, internal audit is a crucial factor in supporting fraud prevention and maintaining the reliability of digital payment systems.